EU grants in the years 2007-2013 and the health care system in Poland - Warchoł, Martyna (Journal of Education, Health and Sport, 2017)
Poland has been a member of the European Union since 1 May 2004 under the Accession Treaty signed on 16 April 2003 in Athens, the legal basis for Poland’s accession to the European Union. Thanks to this move we get help in the form of EU grants to improve our economy. Since then we have seen the effects of this help, such as motorways, stadiums. And what contribution does the EU have for the health of Poland? Thanks to participation in the European Union, our health care has improved. Thanks to numerous subsidies, the conditions in hospitals and outpatient clinics have improved and new medical equipment has become available. The modernization of medical rescue services, including the purchase of new emergency ambulances, the construction, reconstruction or repair of provincial emergency notification centers, will result in the reduction of mortality in emergency situations in the near future. Thanks to subsidies from the European Union, there have been many positive changes in the Polish health service. Thanks to the good use of funds, people are tested with state-of-the-art equipment by qualified medical personnel, brought by specialized ambulances to an appropriately-organized and well-equipped healthcare facility.